Mana rehab : a game that helps in fine motor skills rehabilitation - Lee, Ti Soon (2015)
This research involves the study in the fine motor skills rehabilitation process and implementation of the Skeleton Tracking device Leap Motion in creating a game that is beneficial to the stroke patients. MANA Rehab aims to combine the game elements with the rehabilitation modules to help the stroke patients during fine motor skills rehabilitation progress. The reason for the movement disability caused by stroke is because of the blood supply to the brain is disrupted during stroke and causing the damage to the brain. The damage of the brain can never be recovered, causing disability in body movements. However, the brain is able to adapt with the damage done, and regain of the command in body movement is possible with proper rehabilitation procedures. Currently, there are available projects that include the game elements in the stroke rehabilitation process, but none is specifically dedicated to fine motor skills rehabilitation. Hence, there is lacking in engaging elements to motivate the patients in fine motor skills rehabilitation. In addition, there are uncertainties in defining the suitable hardware to be applied in this context. The objectives of this research is to study the modules of stroke rehabilitation modules, determine the suitable hardware to be implemented in a game that helps in fine motor skills rehabilitation, and lastly, to create a game that is beneficial to the fine motor skills rehabilitation. The scopes in this research limits the system development to focus in fine motor skills rehabilitation, Leap Motion is selected as the skeleton tracking device, and Java Script will be used as the platform if the system development. In the end of the research, a system named MANA Rehab is delivered, combining the Leap Motion functionalities with the fine motor skills rehabilitation modules